Women MSMEs in a Time of Crisis: Assessment of Challenges and Opportunities - Elsa Widia; Sri Mona Octafia (Budapest International Research and Critics University, 2022)
The outbreak of the Covid-19 virus has had a severe impact on Indonesia, this does not only concerns health issues but also extends to all aspects of life, especially the economy and business. In the economic sector, the Covid-19 pandemic feels very deep, because it has destroyed the most important sides of the economy, namely supply and demand. This affects all economic sectors, including MSMEs. It should be noted that MSMEs were able to contribute 57.32 percent to GDP and were able to absorb labor up to 97% in 2018. The importance of the role of MSMEs in the economy is also inseparable from the fact that 64.5% of this sector is managed by women. This research will try to discuss the impact of the COVID-19 crisis on the performance of women MSMEs, as well as explore the innovative strategies adopted by these MSMEs to survive in their business. This study uses quantitative and qualitative methods used in cross-sectional surveys, using questionnaires, and structured interviews to collect primary data. This study focuses on women's MSMEs in the city of Padang, especially in the most extensive sub-district in the city, namely Koto Tangah. The results of the study reveal that the difficult times due to the pandemic have changed the mindset of several MSMEs in Koto Tangah to adopt new marketing strategies. This research will also reveal new marketing strategy opportunities and challenges that need to be a concern for female MSME actors.